Waves over the Arabian Sea during the southwest monsoon (MAUSAM, 1982)
A study of waves over the Arabian Sea was undertaken mainly for the operational purpose of giving wave forecasts for Bombay High area where oil drilling and production has been going on. For the southwest monsoon season of 1976 to 1978 daily observations from the rigs in Bombay High area were available. Thus three years' data have been analysed to study variations of wave parameters with time during monsoon. After the re-opening of Suez canal, the number of ships moving over the Arabian Sea has increased considerably. Moreover, large quantity of data has been collected by the Soviet Research vessels during the Monsoon-1977 experiment. All ships observations for 1977 have been analysed to get an idea of the space variations of wave parameters over the Arabian Sea.